2023
DOI: 10.1111/jcpe.13843
|View full text |Cite
|
Sign up to set email alerts
|

Histological assessment and gene expression analysis of intra‐oral soft tissue graft donor sites

Sandra Stuhr,
Felipe Nör,
Kareem Gayar
et al.

Abstract: AimTo determine the structural and gene expression features of different intra‐oral soft tissue donor sites (i.e., anterior palate, posterior palate, maxillary tuberosity and retromolar pad).Materials and MethodsStandardized mucosal tissue punch biopsies were collected from at least one donor site per subject. Histological processing was performed to determine tissue morphometry and quantify collagen composition. Site‐specific gene distribution was mapped using targeted gene expression analysis and validated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Hence, the best donor site from a histological point of view seems to be the tuberosity, because it has a thick lamina propria without the presence of a smaller submucosal layer [ 6 , 21 ]. Nevertheless, surgical access to this area is difficult and the quantity and shape of connective tissue might be inadequate in some circumstances [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the best donor site from a histological point of view seems to be the tuberosity, because it has a thick lamina propria without the presence of a smaller submucosal layer [ 6 , 21 ]. Nevertheless, surgical access to this area is difficult and the quantity and shape of connective tissue might be inadequate in some circumstances [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The greater capability of tCTG to produce a clinically significant gain in GT is explained by its specific histological and molecular features [15,17,35]. A histomorphometric study by Sthur et al [35] showed a 1.5-2 mm thicker lamina propria in tCTG than in conventional…”
Section: Discussionmentioning
confidence: 99%
“…Both techniques improved the clinical conditions similarly; however, GT showed significantly greater improvement in patients from the CAF + tCTG group. The greater capability of tCTG to produce a clinically significant gain in GT is explained by its specific histological and molecular features [15,17,35]. A histomorphometric study by Sthur et al [35] showed a 1.5-2 mm thicker lamina propria in tCTG than in conventional CTG and a five-fold increase in COL1A1 gene expression in grafts from the maxillary tuberosity, producing denser, thicker tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGGs are generally thicker (Borghetti & Gardella, 1990; Corn & Marks, 1983; Holbrook & Ochsenbein, 1983; Mormann et al, 1981; Soehren et al, 1973) compared to bilaminar techniques using SCTG (Chambrone & Tatakis, 2015; Zucchelli et al, 2010, 2014). The connective tissue layer in FGG, namely the lamina propria, which is underneath the epithelium, is typically formed by a dense network of collagen fibres (Bertl et al, 2015; García‐Caballero et al, 2023; Harris, 2003) whose biological and structural properties seem to vary depending on the donor site (Stuhr et al, 2023). Additionally, it has been shown that the lamina propria has two distinct layers: (i) the papillary layer; and (ii) the reticular layer that presents a higher collagen density (García‐Caballero et al, 2023).…”
Section: Discussionmentioning
confidence: 99%